Work Environment and Perception of Institutional Policies as Correlates of Lecturers’ Productivity in Uganda Christian University - Naikote, B.; Bakkabulindi, F. E. K (African Journals Online (AJOL), 2011)
This study sought to establish the relationship between each of work environment and perception of institutional policies and lecturers’ productivity in Uganda Christian University. It involved 94 lecturers who responded to a self administered questionnaire. Data analysis was based on percents and means at the descriptive level while Pearson’s correlation coefficient was used to correlate the independent variables with productivity. The results revealed that there was no significant relationship between work environment and the productivity of lecturers, hence the recommendation that other than work environment, the University should prioritize factors such as qualification, experience, remuneration and training. The results revealed that there was a significant positive relationship between perception of institutional policies and productivity, hence the recommendation that the University embraces favourable policies that balance institutional and individual needs.